Research Progress of Exopoly Saccharide Produced by Microorganisms - LI Jia-xin; YANG Yu-xia; TAO Ran; CUI Jin-xi; MAO Peng; ZHAO Xiu-hong (Liang you shipin ke-ji, 2024)
In recent years, exopoly saccharides (EPS) produced by microorganisms have garnered attention due to their functional properties such as improving food quality, regulating intestinal microbiota, antioxidative effects, anticancer properties, immunoprevention, and treatment of cardiovascular diseases. Currently, research on microbial EPS (extracellular polymeric substances) in China is still in its early stages and requires further exploration. This paper comprehensively reviewed the latest advancements in the classification, biosynthesis, structural modification, functional properties, and applications of EPS produced by microorganisms both domestically and internationally. This study also focused on analyzing the biosynthetic pathways and structural features of different types of EPS, as well as the strategies for functional modification through physical, chemical, and biological methods. The aim is to provide new references and guidance for research and development in relevant fields, thereby promoting the application and industrialization of EPS in the food, pharmaceutical, and industrial sectors.